Relationship of Mother's Knowledge, Partner Support and Health Worker Support with The Compliance of Pregnant Mothers in Consuming Iron (Fe) Tablets at Sikumana Puskesmas, Kupang City - Florentina Dhone; Sigit Purnawan; Amelya B. Sir (Universitas Nusa Cendana, 2022)
Anemia in pregnant women have impact on the health of pregnant women and the fetus during pregnancy, bleeding, prolonged labor, low birth weight, congenital defects, abnormalities in the growth of the body and brain cells in the fetus, miscarriage, premature birth and even death. The prevalence of anemia in pregnant women in 2019 in Kupang City was 2,850 pregnant women with the highest proportion of anemia in the Sikumana Health Center area, namely 960 pregnant women. The purpose of this study to analyze the relationship between knowledge, husbands support, and health workers support with compliance of pregnant women in consuming iron tablets at the Sikumana Community Health Center, Kupang City. The cross sectional method was used in this study. The population in this study were pregnant women at Sikumana Health Center who received iron tablets in October-November 2020 namely as many as 97 people, and the sampling technique used simple random sampling with a sample size of 75 people. Data analysis using the Chi-Square statistical test with a 95% confidence level. The results of the analysis showed that there was a relationship between the knowledge variable (p-value=0.010), husband's motivation (p-value=0.001), and the motivation of health workers (p-value=0.008) with compliance with the consumption of iron tablets for pregnant women in the Sikumana Community Health Center Kota Kupang in 2020. Suggestions for health workers to implement a monitoring card for Fe tablet supplements to determine the process of consuming, the number consumed, and the time consuming.